IDENTIFIKASI PERMASALAHAN FINANSIAL PADA JAMINAN SOSIAL KESEHATAN NASIONAL - Mas'udin, Mas'udin (Polytechnic of State Finance STAN, 2017)
The national social health security program (JKN) is a government program that aims to provide social insurance of health care for all Indonesian people. Within three years of implementation, the JKN program has provided many benefits to the community. However, there is a financial problem indicated by the financial statements of social health insurance program, which is estimated experiencing financial distress. This study aims to identify financial problem of social health insurance program. The research used mix method that is quantitative and qualitative method with sequence explanatory design. Data is taken from Healthcare and Social Security Agency (BPJS) financial statement year 2014 - 2016, and analyzed using Altman (Z-Score) model and Zmijewski (X-Score) model. The result of the study shows that the social health security program has financial distress.Â Program jaminan kesehatan nasional (JKN) merupakan program Pemerintah yang bertujuan memberikan kepastian jaminan kesehatan yang menyeluruh bagi seluruh rakyat Indonesia. Dalam tiga tahun pelaksanaannya, program JKN telah memberikan banyak manfaat bagi masyarakat. Namun laporan keuangan program jaminan sosial kesehatan menunjukkan adanya permasalahan finansial, yang diduga mengalami financial distress. Penelitian ini bertujuan untuk mengidentifikasi permasalahan finansial program jaminan sosial kesehatan. Metode penelitian yang digunakan mix method, yaitu kuantitatif dan kualitatif dengan desain urutan pembuktian (sequential explanatory). Data bersumber dari laporan keuangan BPJS Kesehatan tahun 2014 s.d 2016, dan dianalisis menggunakan model Altman (Z-Score) dan model Zmijewski (X-Score). Hasil studi menunjukkan bahwa Program Jaminan Sosial Kesehatan mengalami financial distress.